Osteoporosis’s undertreatment in Pakistan - Muhammad Tawab Khalil; Farooq Azam Rathore; Osama Ahmed (Journal of the Pakistan Medical Association, 2024)
Dear Editor, We have read the letter to the editor by Atiq et al., with interest. They have correctly highlighted that osteoporosis is a silent killer and majority of the patients are diagnosed only when they already have a fragility fracture.1 The authors have highlighted important measures to improve awareness of osteoporosis among general population and doctors like arranging seminars, establishment of hotlines and formation of a national committee. They have mentioned the lack of local guidelines for management of post-menopausal osteoporosis. We would like to update the readers that clinical practice guidelines regarding osteoporosis with 50 recommendations considering the local Pakistani context have recently been published.2 The authors adopted the “clinical practice guidelines for the diagnosis and treatment of postmenopausal osteoporosis—2020 update from American Association of Clinical Endocrinology” to adapt to the local context by using GRADE-ADOLOPMENT process.2